Lecture 07. Acids and Bases. Pt. 4. - Arasasingham, Ramesh D. (University of California Irvine (UCI), 2013)
UCI Chem 1C General Chemistry (Spring 2013)
Lec 07. General Chemistry -- Acids and Bases -- Part 4

Instructor: Ramesh D. Arasasingham, Ph.D.

Description: UCI Chem 1C is the third and final quarter of General Chemistry series and covers the following topics: equilibria, aqueous acid-base equilibria, solubility equilibria, oxidation reduction reactions, electrochemistry; kinetics; special topics.

Index of Topics:
0:00:00 Review of Carbonic Acid Example
0:15:43 Hydrolysis
0:18:10 Acid Base Properties of Salt
0:39:00 Calculating pH of Salt
0:47:09 Arranging Compounds from Most Acidic to Most Basic
Keywords: Chemistry